1984
DOI: 10.1111/j.1365-2389.1984.tb00298.x
|View full text |Cite
|
Sign up to set email alerts
|

The forms of occurrence of manganese in some acidic soils

Abstract: The forms of occurrence of Mn were examined in some acidic surface and sub-soils from areas of permanent grassland using chemical extractants. Despite high total contents of Mn in some of the soils and low pH, only minor proportions occurred as exchangeable Mn2+. Much larger proportions were present as reducible hydrous oxides, e.g. up to 38% and 54% of the total contents in surface and subsoils, respectively, were present as hydroquinone extractable, or easily reducible, Mn. Reducible forms ofMn were poorly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…McKenzie (1970McKenzie ( , 1972 has demonstrated the specific nature of the reaction of Co with Mn oxide minerals and suggested that CoL+ is first oxidized to Co3+, which then replaces Mn3+ where this has substituted for Mn4+ in the lattice. If this is the case, the reaction of hydroquinone with the most reactive forms of MnO, would release only limited amounts of the Co. On average, over 70% of the total Mn oxides in the present soils was not extracted with hydroquinone and was presumably present in unreactive forms, or in an occluded, inaccessible state (Jarvis, 1984). Furthermore, the data from the concretions, although from only two soils, indicate that high proportions of the total soil Co will be held within discrete Mn particles, and released only by the action of prolonged or strong reduction.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…McKenzie (1970McKenzie ( , 1972 has demonstrated the specific nature of the reaction of Co with Mn oxide minerals and suggested that CoL+ is first oxidized to Co3+, which then replaces Mn3+ where this has substituted for Mn4+ in the lattice. If this is the case, the reaction of hydroquinone with the most reactive forms of MnO, would release only limited amounts of the Co. On average, over 70% of the total Mn oxides in the present soils was not extracted with hydroquinone and was presumably present in unreactive forms, or in an occluded, inaccessible state (Jarvis, 1984). Furthermore, the data from the concretions, although from only two soils, indicate that high proportions of the total soil Co will be held within discrete Mn particles, and released only by the action of prolonged or strong reduction.…”
Section: Discussionmentioning
confidence: 85%
“…There is therefore a need for a simple, rapid technique to determine the extent to which Co is associated with Mn in British soils. Chemical extractants have been used for many years to estimate specific forms of soil Mn (Leeper, 1947;Jones & Leeper, 195 1;Heintze & Mann, 1951;Chao, 1972;Jarvis, 1984). In the present study, the relationship between Co and the most reactive form of oxidized Mn (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…We used Mn extracted by acid ammonium oxalate (Mn o ) as described above to approximate total Mn oxides (Jarvis 1984). Oxalate, however, is also likely to extract Mn bound to organic matter.…”
Section: Total Mn Oxidesmentioning
confidence: 99%
“…In soil M, Mn content was similar in the Fe oxide and organically bound fractions. In both soils the exchangeable Mn fraction was the lowest; our values for exchangeable Mn were also lower than those found in acid soils (Jarvis, 1984). The exchangeable Mn fraction has been shown to fall markedly with rising pH (Sims, 1986), suggesting that the alkaline reaction of our soils may have been responsible for the low levels of exchangeable Mn recorded.…”
Section: Resultsmentioning
confidence: 56%